Pengaruh behavioural conflict dan negative affect state terhadap employee wellbeing dan dampaknya terhadap job satisfaction pada karyawan PT. Iron Bird Logistics - Ayu Raihani, Irbah; Tanuwijaya, Justine; Tamara, Anna; Bagus Aristo, Agra; Hakki Mirici, Ismail (Jurnal Riset Pendidikan Ekonomi, 2024)
This study aims to analyze the influence of behavioral conflict, negative affect state, employee wellbeing on job satisfaction at PT. Iron Bird Logistics. This research uses quantitative research methods. Data was collected from 231 employees working at PT. Iron Bird Logistics, analysis data method in this study is simple linear regression analysis with AMOS software. The results of testing the hypothesis in this study indicate that there is no negative effect on behavioral conflict on employee wellbeing and negative affect state on employee wellbeing, but there is a positive effect on employee wellbeing on job atisfaction. From this study it is hoped that companies can pay attention to problems that occur to employees in company in order to meet employee job satisfaction.